Associations of loneliness and social isolation with physical and mental health among adolescents and young adults. (July 2021) - Christiansen, J; Qualter, P; Friis, K; Pedersen, SS; Lund, R; Andersen, CM; Bekker-Jeppesen, M; Lasgaard, M
Aims: The present study investigates whether loneliness and social isolation are associated with poor physical and mental health among adolescents and young adults, and whether age and gender play a role in the associations of loneliness and social isolation with mental and physical health. Methods: This study used cross-sectional self-report data from the 2017 Danish Health and Morbidity Surveys titled 'How are you?' ( N = 19, 890, M = 22.6 years). Results: Logistic regression analyses showed that loneliness and social isolation were independently associated with poor physical and mental health. Loneliness was associated with increased odds of asthma, migraine, osteoarthritis, rheumatoid arthritis, hypertension, slipped disc/back pain, tinnitus, long-term mental illness, depressive symptomatology, anxiety symptomatology and alcohol problems. Social isolation was associated with decreased odds of having migraine, osteoarthritis and alcohol problems, and an increased risk of long-term mental illness and depressive symptomatology. Small age and gender differences were detected. Conclusions: In adolescents and young adults, loneliness and social isolation were associated with poor mental health and loneliness with poor physical health. These findings highlight the need for targeted prevention and intervention initiatives to alleviate loneliness and social isolation.